Investigation of tidal stream energy in the straits of Malacca / Chandra Bhushan Roy - Chandra, Bhusan Roy (2016)
Tidal stream energy is a type of marine renewable energy. Malaysia being maritime country with long coastline has potential to harness tidal stream energy. Therefore, it is crucial to investigate tidal stream energy and its potential for Malaysia. This study investigates tidal stream energy in the Straits of Malacca. This work focus on the Straits of Malacca since its vicinity to highly populated west coast of Peninsular Malaysia. In addition, the Straits provide narrow passage to sea water, which converge tidal flows. Literature review found limited information on distribution of tidal flow and energy in the Straits of Malacca. Therefore, first this study gives information on distribution of tidal flow in the Straits of Malacca. Second, it identifies sites and their potential for harnessing tidal stream energy. A three-dimensional finite-difference numerical model was used to model flow in the Straits of Malacca. The flow in the Straits of Malacca is governed by sea surface wind, semi-diurnal tide and stratification along continental shelf. This study carried out statistical analysis and found good correlation between the model results and field data at the tidal stations. Further model results were also compared with previous research works. The Straits of Malacca receives semi-diurnal tide with two high and two lows on each day. Tidal flow speed varies from 0.1 m/s to 1.7 m/s across the Straits of Malacca. Four zones were considered for analysing distribution of tidal stream energy in the Straits of Malacca. Investigation identified that the southern and central part of the Straits have suitable sea depth, flow speed and tidal stream energy. Extractable tidal stream energy in the Straits of Malacca varies from 64 W/m2 to 2516 W/m2. This study identified three sites for extracting tidal stream energy. The sites being off the coast of Pangkor Island, port Klang and Malacca. Site near coastline of the Pangkor Island have depth of 35 m and receive peak tidal energy flux 1406 W/m2. Port Klang provide depth of 25 m and receive 1406 W/m2 of peak tidal energy flux. Malacca coastline provides depth of 20 m and receives 2516 W/m2 of peak tidal energy flux. Further, this investigation calculated available and extractable power using two configurations of tidal current turbines. Single tidal current turbine configuration considered vertical axis Gorlov, and horizontal axis Open Hydro turbines. It found that the Gorlov turbine efficiently extracts available tidal stream energy. The Gorlov turbine perform with average capacity factor of 28%, while Open Hydro under performs with an average capacity factor of 2.25 per-cent. The study also estimates that a three-row configuration of tidal current farm with 500 units can produce 19610 Mwh, 18730 Mwh, and 17930 Mwh of electricity annually at Malacca city coastline, Port Klang, and Pangkor Island respectively. This study successfully used numerical model to investigate tidal stream energy. This investigation finds that the Straits of Malacca is suitable for extracting tidal stream energy. At the identified sites Straits of Malacca provides suitable sea-depth, flow speed and tidal current energy.